Restrukturisasi dan Revitalisasi Keuangan PT. X - , Haris Gunawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The focus of this study is to know capital structure and how much fund that company X needed. This research is qualitative with using several analysis technique such as financial ratio, common size analysis, cross section analysis, free cash flow analysis and AFN. The research shows that to improve company performance, company X can evaluate or reidentification of their asset, suppress the using of short term loan. and renegotiate interest rate of short term loan.